Comprehensive Proteomic Analysis of Lysine Acetylation in Nicotiana benthamiana After Sensing CWMV Infection - Yuan, Bowen; Liu, Tingting; Cheng, Ye; Gao, Shiqi; Li, Linzhi; Cai, Linna; Yang, Jian; Chen, Jianping; Zhong, Kaili (Frontiers in Microbiology, 2021)
Protein lysine acetylation (Kac) is an important post-translational modification mechanism in eukaryotes that is involved in cellular regulation. To investigate the role of Kac in virus-infected plants, we characterized the lysine acetylome of Nicotiana benthamiana plants with or without a Chinese Wheat Mosaic Virus (CWMV) infection. We identified 4803 acetylated lysine sites on 1964 proteins. A comparison of the acetylation levels of the CWMV-infected group with those of the noninfected grouprevealed that 747 sites were upregulated on 422 proteins, including chloroplast localization proteins and histone H3, and 150 sites were downregulated on 102 proteins. Nineteen conserved motifs were extracted: 51% of the identified proteins were localized to the chloroplast. Among the acetylated proteins, 19 Kac sites were combined in core histones, including 10 Kac sites on histone 3. Bioinformatics analysis revealed that Kac occurs on a diverse range of proteins involved in a wide variety of biological processes, especially photosynthesis. Furthermore, we demonstrated that the acetylation level of histone 3, chloroplast proteins and some metabolic pathway-related proteins were significantly higher in CWMV-infected plants than in noninfected plants. In summary, our results reveal the regulatory roles of Kac in response to CWMV infection.